In vitro study of red beetroot ethanol extract (Beta vulgaris L.) as xanthine oxidase inhibitor - Gita Almira Putri; Agung Nova Mahendra; I Made Jawi (DiscoverSys Inc., 2021)
Background: Xanthine oxidase (XO) is an enzyme that catalyzes the oxidation of xanthine to uric acid. Hyperuricemia is a condition in which uric acid levels in the blood are > 6.8 mg/dL. Hyperuricemia is managed by administering uric acid-lowering drugs that work by inhibiting the activity of XO. Allopurinol, as the first-line drug, has several side effects. Flavonoids and betalains have been shown in numerous studies to have the ability to inhibit XO. The purpose of this study is to examine the ethanol extract of red beetroot (Beta vulgaris L.) with its flavonoids and betalains content in inhibiting the activity of XO. Methods: This study was an in-vitro experimental study using UV-Vis spectrophotometry (ë 285 nm). Red beetroot was extracted with 96% ethanol solvent using the maceration method. Allopurinol was used in this study as a positive control. This study was carried out in triplicates, with a test sample consisting of 5 different concentrations. The results of this study were analyzed using the Kruskal Wallis.Results: The ethanol extract of red beetroot inhibits XO enzymatic activity (55.11%) at 1000 ?g/ml. There was a statistical difference between the control group, the ethanol extract of red beetroot group, and the allopurinol group in the inhibition of XO enzyme activity (p= 0.001).Conclusion: The ethanol extract of red beetroot (Beta vulgaris L.) can inhibit xanthine oxidase (XO).